Dosimetric comparison of three-dimensional conformal radiotherapy, intensity modulated radiotherapy, and helical tomotherapy for lung stereotactic body radiotherapy - Kinhikar, Rajesh; Ghadi, Yogesh; Sahoo, Priyadarshini; Laskar, Sarbani; Deshpande, Deepak; Shrivastava, Shyam; Agarwal, Jaiprakash (Journal of medical physics, 2015)
To compare the treatment plans generated with three-dimensional conformal radiation therapy (3DCRT), intensity modulated radiotherapy (IMRT), and helical tomotherapy (HT) for stereotactic body radiotherapy of lung, twenty patients with medically inoperable (early nonsmall cell lung cancer) were retrospectively reviewed for dosimetric evaluation of treatment delivery techniques (3DCRT, IMRT, and HT). A dose of 6 Gy per fraction in 8 fractions was prescribed to deliver 95% of the prescription dose to 95% volume of planning target volume (PTV). Plan quality was assessed using conformity index (CI) and homogeneity index (HI). Doses to critical organs were assessed. Mean CI with 3DCRT, IMRT, and HT was 1.19 (standard deviation [SD] 0.13), 1.18 (SD 0.11), and 1.08 (SD 0.04), respectively. Mean HI with 3DCRT, IMRT, and HT was 1.14 (SD 0.05), 1.08 (SD 0.02), and 1.07 (SD 0.04), respectively. Mean R50% values for 3DCRT, IMRT, and HT was 8.5 (SD 0.35), 7.04 (SD 0.45), and 5.43 (SD 0.29), respectively. D2cmwas found superior with IMRT and HT. Significant sparing of critical organs can be achieved with highly conformal techniques (IMRT and HT) without compromising the PTV conformity and homogeneity.